Analysis of PBL-based LKPD Development Needs to Improve Critical Thinking Ability in Indonesian Language Learning - Pane, Syafitria Rahma; Herpratiwi, Herpratiwi; Rusminto, Nurlaksana Eko; Sutiarso, Sugeng (BIRCU, 2023)
This research aims to develop a PBL model-based LKPD on Indonesian language subjects in SDNI Pelita class IV. The method in this research is research and development using the ADDIE development model. Collecting research data using evaluation leaflets and test questions. This research phase focuses on the analysis phase for the development of PBL based LKPD to enhance the ability to think critically about the Indonesian language learning of 1 Pelita State Elementary School students. Consider some important points, including 1) Students struggle to analyze, evaluate, and interpret text readings. 2) Students find it challenging to make argumentative solutions from the wrong text; 3) Teachers need to use LKPD teaching materials for the learning process. The results of the literature analysis have been obtained that for the implementation of the PBL-based LKPD in implementation the study refers to the sixth step: 1) Preparation; 2) Observation; 3) Analysis of problems; 4) Formulation of a solution plan; 5) Presentation of results of work; 6) Reflection and evaluation. Critical thinking skills indicators in this study focus on text analysis, text argument evaluation, text interpretation, critical information in text and problem-solving.